Дискурсивні аспекти динаміки української мови в контексті активних мовних процесів у слов’янському світі - Радзієвська, Т.В. (Мовознавство, 2013)
У статті висвітлюється питання про роль дискурсу в сучасних процесах розвитку мови, які розглядаються на тлі глобалізаційних змін і зростання ролі інформації в соціокомунікативному середовищі. Основну увагу приділено мас-медійному (газетному) дискурсу та його впливу на активні процеси в українській мові. Аналіз сучасних інновацій охоплює синтаксис речення (структури, що репрезентують мовленнєву подію), категорію модальності (розглядається питання щодо віртуальної модальності), семантику (питання семантичного розвитку одиниць непредметного значення). The article examines the role of discourse in recent processes of language development which
are regarded through general globalization changes and growing value of information in socio-communicative
space. The article reveals that discourse in modem Slavonic languages does not only
serve as a linguistic and communicative environment for the realization of speech activity and creation
of texts, but is also a factor that influences the functioning of lexical and syntactic units and promotes
certain innovative mechanisms in semantics, syntax, pragmatics.
The shift and concentration of linguistic processes in the idiom of literary language from the discourse
of fiction to mass media is one of the essential features of the linguistic situation in Slavonic
languages, which defines the character of linguistic reality at the lexical, syntactic, semantic and
other levels of language. The article also focuses at some phenomena and tendencies in Ukrainian in
the last decade. Within the domain of sentential syntax the trend for generating new types of syntactic
structures is investigated. Present day Ukrainian mass media texts are used to explain the variable
character of syntactic structures representing a speech event, the development of syntactic techniques
is dependent on the information processes streamlining. There are 11 types of syntactic units
identified which reflect the syntagmatic potential of the language and possibilities for developing
linguistic means for reproducing «author’s» and «non-author’s» components within one utterance.
Pragmatic specifics of mass media text production, which is determined by the combination of
two tasks: to inform and to provide attractive information, generates the trend to produce means
of virtual modality that combine semantic features of realis and irrealis. It is proved that the bearer
of such meaning in modem mass media is нібито «allegedly» which creates a two-dimensional picture
of the situation and ignores the issue of its credibility. In the functional aspect this word shows
properties of the loosely governed member which is usually attached to the whole phrase and not to a
separate word; as a modal word it creates the effect of imaginary co-existence of the two version of
the event described.
Active semantic processes are investigated using the units with abstract meaning which are
found in the newspaper texts of the recent decade and display new semantic features, sometimes additional
meanings. The word гра «play, game» — a concept belonging to the sphere of social activity
— is used to demonstrate that during the adaptation to the new reference sphere and extension of
the nominative possibilities the semantic features of the word are augmented, the character of these
semantic features being directly in line with the tasks and functions of the mass media discourse.
The investigated phenomena show that while applying modem approach to the study of language dynamics
it is necessary to take into account the factor of discourse specifics.